2018
DOI: 10.1007/s00253-018-9317-6
|View full text |Cite
|
Sign up to set email alerts
|

Biochar carrier application for nitrogen removal of domestic WWTPs in winter: challenges and opportunities

Abstract: Biofilm processes have a better nitrogen removal ability than traditional activated sludge at low temperatures (< 15 °C). Many biofilm processes, as well as integrated biofilm and activated sludge processes, are potential and realizable nitrogen removal upgrading methods for domestic wastewater treatment plants (WWTPs). Therefore, biofilm packing material is attractive for domestic WWTP upgrading and reconstruction in winter. For a half decade, researchers have successfully applied activated carbon to biochar … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 26 publications
(12 citation statements)
references
References 66 publications
0
12
0
Order By: Relevance
“…A limited number of studies have explored biochar application in wastewater treatment process for N removal (He, Ding, Wang, et al., 2018). In this review, we mainly focus on soil‐based biofiltration systems with similar configurations (trickling filter, CW, and SWIS) that have incorporated biochar for N removal from on‐site wastewater (Table 1).…”
Section: Application Of Biochar In Biofiltration Systems For N Removalmentioning
confidence: 99%
See 1 more Smart Citation
“…A limited number of studies have explored biochar application in wastewater treatment process for N removal (He, Ding, Wang, et al., 2018). In this review, we mainly focus on soil‐based biofiltration systems with similar configurations (trickling filter, CW, and SWIS) that have incorporated biochar for N removal from on‐site wastewater (Table 1).…”
Section: Application Of Biochar In Biofiltration Systems For N Removalmentioning
confidence: 99%
“…At low temperatures, biochar‐amended CWs also showed better performance compared with the conventional wetland (He et al., 2018b; He, Ding, Wang, et al., 2018). For example, during winter (4.9 °C), CWs with 10 and 20% (v/v) biochar amendment achieved 85.7 ± 6.2 and 91.7 ± 3.8% TN removal, which was statistically significantly higher than the conventional CW (73.6 ± 9.6%); this result was possibly due to the labile organic C released from biochar for denitrification (J. Li et al., 2019).…”
Section: Application Of Biochar In Biofiltration Systems For N Removalmentioning
confidence: 99%
“…Biochar both adsorbs recalcitrant organic matter and provides an attachment surface for microbial biofilms. 26,33 The adsorbed recalcitrant organic matter may be slowly degraded to simple organic molecules by hydrolytic bacteria and then consumed by either denitrifiers in the anoxic stage or aerobic heterotrophs in aerobic stage, thus regenerating the active adsorption sites on the biochar surface. Prior studies showed that activated carbon can be bioregenerated in situ by organic matter degradation and desorption.…”
Section: Effects Of Adsorbent Addition and Hrt On Sbbr Performance Scodmentioning
confidence: 99%
“…In addition, prior studies also showed that biochar can provide an attachment surface for biofilm growth in wastewater treatment systems. 26,27 Both zeolite and biochar are promising materials for enhancing biological treatment of domestic wastewater, yet studies of the combined use of these materials for landfill leachate treatment have not been carried out previously. Hence, the overall goal of this study was to enhance N, COD and color removal from landfill leachate in SBBRs amended with zeolite and biochar.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, studies have shown that dissolved organic matter (DOM) discharged from biochar prepared from almond, walnut shell, wheat straw, and so on could be a carbon source available to organisms, thus improving denitrification efficiency. Hydrochar can affect the range and activity of microorganisms in wastewater treatment plants (WWTPs), thereby enhancing denitrification. After biological treatment in WWTPs, the spent hydrochar can be further used in soil remediation. , However, these studies are individual in nature and are usually limited to one application of hydrochar, resulting in the waste of resources. It is not known how well hydrochar can be applied to a wastewater treatment and soil conditioning system if the two applications are combined in a series.…”
Section: Introductionmentioning
confidence: 99%